Does the type of maltreatment matter? Assessing the individual and combined effects of multiple forms of childhood maltreatment on exclusive breastfeeding behavior. (December 2018) - Islam, Md. Jahirul; Mazerolle, Paul; Broidy, Lisa; Baird, Kathleen
Abstract: Background: Childhood maltreatment (CM) has been associated with a range of adult health outcomes; however, extant research has focused more on exposure to a single form of abuse rather than multiple forms. Moreover, very few studies have specifically investigated the impact of CM on exclusive breastfeeding (EBF) outcomes. Objectives: This study aims to examine: (1) the individual and combined effects of multiple forms of CM on EBF outcomes; and (2) whether postpartum depression and maternal stress act to mediate or moderate the association between CM and EBF. Method: Cross-sectional survey data were collected between October 2015 and January 2016 from 426 women of Bangladesh who were six months postpartum. Results: Based on the adjusted multivariate logistic regression model, women who experienced childhood sexual abuse (CSA) were significantly less likely to exclusively breastfeed babies than their non-abused counterparts (AOR: 0.38, 95% CI [0.15, 0.92]). When a composite measure was created to examine the additive effects of adverse childhood experiences, a dose-response association was observed between the reported number of different types of CM and early termination of EBF. Though experiencing postpartum depression and maternal stress do not mediate the effect of CSA on EBF, they do moderate them such that the odds of early termination of EBF are notably higher among women who experienced CSA in combination with postpartum depression or high levels of stress. Conclusions: Findings from this study offer some insight into the intergenerational effects associated with CM experiences, and underpin the need for effective policies and programs to prevent or reduce its occurrence and improve the EBF outcomes.